Efeito luminal da angiotensina sobre a secreção de potássio em túbulos distais de rim de ratos - Amorim, José Benedito Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The effect of luminal ANGII on K+ secretion by late distal tubule (connecting segment and initial cortical collecting duct) was studied using in vivo stationary microperfusion and K-sensitive microelectrode techniques. Luminal perfusion of ANG II reduced Jk+ from a control value of 0.90±0.19 (n=12) nmol/cm2.s to 0.51±0.05, n=9, (10-12M), 0.70±0.22, n=27 (10-11M) and 0.63±0.08, n=12 (10-9M) nmol/cm2.s (p<0.05 by paired t-test). However, high doses of ANGII (10-6M) had no significant effect on Jk+. Losartan 10-6M, a non-peptide AT1 receptor blocker, reverted the inhibitory effect of ANGII. To test the possibility that the PLA2/arachidonic acid/PGE2 pathway, which had been shown to inhibit other transport mechanisms, is involved in ANGII-mediated cellular signaling cascades, PGE2 was perfused luminally (Jk+ control = 0.93±0.08, n=12 nmol/cm2.s; 10-9M PGE2, Jk+ = 0.55±0.05, n-12; 10-6M PGE2, Jk+ = 0.47±0.04), n=12; both doses reduced K+ secretion significantly (p<0.01). Perfusing with Indomethacin, an unspecific blocker of the PLA2/arachidonic acid/PGE2 path, (10-5M), plus ANG II (10-9M), JK+ increased to 0.95±0.12 (n=13) nmol.cm-2.s-1 compared to ANG II alone (Jk+ = 0.63±0.05, (n=13) nmol/cm2.s, p<0.05). During luminal perfusion with Indomethacin alone, no significant effect on K+ secretion was seen (Jk+ control = 0.73±0.05 (n=10) nmol/cm2.s, 10-6M INDO Jk+ = 0.63±0.07 (n=10), P>0.19. In conclusion, ANG II is able to regulate distal K+ secretion when applied to the tubule lumen, probably via AT1 receptors; it is suggested that the signalling path of the inhibitory effect of ANG II may involve PLA2/arachidonic acid/PGE2

Estudamos o efeito da Angiotensina II sobre a secreção de potásssio em túbulo distal final (segmento conector e duto coletor cortical) através da técnica de microperfusão estacionária in vivo e mensuração da atividade catiônica por meio de microeletrodos contendo resina de troca iônica sensível a K+. A perfusão luminal com ANG II reduziu o fluxo secretório de potássio (JK+) observado no grupo controle de 0.90±0.19 nmol/cm2.s, n=12, para 0.51±0.05, n=9, (ANG II 10-12M), 0.70±0.22, n=27 (ANG II 10-11M) e 0.63±0.08 nmol/cm2.s, n=12 (ANG II 10-9M); (p<0.05 teste t pareado). Entretanto, na presença de dose elevada de ANG II (10-6M) não observamos efeito significante sobre o JK+. A presença de Losartan (10-6M), um bloqueador não peptídico do receptor AT1 reverteu o efeito inibitório da ANG II. No intuito de se avaliar a possibilidade da via PLA2/ácido araquidônico/PGE2 participar deste processo de regulação celular, uma vez que tais agentes participam da inibição de outros mecanismos de transporte que envolve a ativação da sinalização celular mediada por Angiotensina II, perfundimos luminalmente PGE2 o qual inibiu o fluxo secretório de K+ em ambas doses utilizadas no presente trabalho; Jk+ controle = 0.93±0.08 nmol/cm2.s, n=12 para 0.55±0.05 nmol/cm2.s, n=12 (PGE2 10-9M) e 0.47±0.04 nmol/cm2.s, (PGE2 10-6M), n=12, (p<0.01). A perfusão com Indometacina (10-5M), bloqueador inespecífico da via PLA2/Ácido Araquidônico/PGE2 associado a Angiotensina II (10-9M) aumentou o JK+ (0.95±0.12 nmol.cm-2.s-1, n = 13) quando comparado a perfusão isolada de ANG II (10-9M) (Jk+ = 0.63±0.05 nmol/cm2.s, n = 10); (p<0.05). Concluímos que a ANG II inibiu luminalmente a secreção distal de K+ provavelmente acoplado ao receptor AT1 e este efeito pode ser mediado pela via PLA2/Acido Araquidônico/ /PGE2.
Keywords: Angiotensina; Potassio; Rins; Angiotensin; Potassium; Kidneys